2003
DOI: 10.1021/ef0301396
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Vacuum Gas Oil Based on Chemical Oxidation Followed by Liquid−Liquid Extraction

Abstract: Desulfurization of vacuum gas oil (VGO) has been investigated based on chemical oxidation of sulfur-containing compounds using H 2 O 2 and acetic acid (AcOH), followed by extraction of the oxidized compounds from the resulting VGO using an aqueous acetonitrile solution. The desulfurization behavior of VGO was compared with that of light oil feedstocks, and the reactivities of the individual sulfur compounds in VGO were studied by field ionization-mass spectrometry (FI-MS) analysis. By use of the desulfurizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 11 publications
(48 reference statements)
0
38
0
Order By: Relevance
“…Studies have shown that hydrogen peroxide appears to be a promising oxidizing agent in the catalyzed oxidation of sulfur compounds in fuels due to the fact that it offers a high amount of active oxygen and produces only water as a by-product. [18][19][20][21][22][23][24][25] The activity and selectivity of metal complexes immobilized on polymer microspheres have been reported in our previous studies to be as efficient as unsupported metal complexes. [26][27][28][29] In an attempt to improve the surface area of the polymeric support, electropsun polymer fibres have also been reportedly employed as an alternative.…”
Section: Introductionmentioning
confidence: 73%
“…Studies have shown that hydrogen peroxide appears to be a promising oxidizing agent in the catalyzed oxidation of sulfur compounds in fuels due to the fact that it offers a high amount of active oxygen and produces only water as a by-product. [18][19][20][21][22][23][24][25] The activity and selectivity of metal complexes immobilized on polymer microspheres have been reported in our previous studies to be as efficient as unsupported metal complexes. [26][27][28][29] In an attempt to improve the surface area of the polymeric support, electropsun polymer fibres have also been reportedly employed as an alternative.…”
Section: Introductionmentioning
confidence: 73%
“…The alkyl sulfide is a neutral liquid substance, and the disulfide has a poor stability. Both are prone to be oxidized to sulfoxide or sulfonic acid [17], and then removed by extractant. As shown in Table 3, alkylthiophene (96.18 %), benzothiophene (42.95 %) and dibenzothiophene (35.38 %) in gasoline–diesel fraction have been removed after oxidative–extractive reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Gore et al (2003) developed a patent in which peracetic acid was used as an oxidant for CODS of light atmospheric gas oil (LAGO) and at the same time using 2 parts H 2 O to 98 parts AcOH as an extraction solvent SR of 82% was achieved at 15°C. In another work presented by Shiraishi and Hirai (2004), the viscosity of VGO was reduced by diluting it with n-decane and subsequently oxidizing with peroxyacetic acid at 70°C. The generated sulfones were then extracted using ACN (84%).…”
Section: Organic and Inorganic Acidsmentioning
confidence: 99%